1993
DOI: 10.1289/ehp.93101s373
|View full text |Cite
|
Sign up to set email alerts
|

Indications of repair of radon-induced chromosome damage in human lymphocytes: an adaptive response induced by low doses of X-rays.

Abstract: Naturally occurring radon is a relatively ubiquitous environmental carcinogen to which large numbers of people can be exposed over their lifetimes. The accumulation of radon in homes, therefore, has led to a large program to determine the effects of the densely ionizing a particles that are produced when radon decays. In human lymphocytes, low doses of X-rays can decrease the number of chromatid deletions induced by subsequent high doses of clastogens. This has been attributed to the induction of a repair mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 48 , 53 A combination of a low LET (X-rays) priming dose and a high LET (α-particles of radon gas) challenge dose leads to adaptation in human lymphocytes. 54 , 55 In cellular studies, values of priming doses and dose rates resulting in adaptive responses seem to be located within certain ranges. 46 , 51 , 56 , 57 , 58 Consequently, no adaptive response is seen with priming doses or dose rates outside this window.…”
Section: Discussionmentioning
confidence: 99%
“… 48 , 53 A combination of a low LET (X-rays) priming dose and a high LET (α-particles of radon gas) challenge dose leads to adaptation in human lymphocytes. 54 , 55 In cellular studies, values of priming doses and dose rates resulting in adaptive responses seem to be located within certain ranges. 46 , 51 , 56 , 57 , 58 Consequently, no adaptive response is seen with priming doses or dose rates outside this window.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences have suggested various possible pathways mediating RAR. For example, it was reported that the expression and transcription of some specific genes participating in DNA repair and cell cycle regulation were required for RAR in human lymphocytes [31] , [32] , [33] . It was also shown that RAR was inhibited by 3-aminobenzamide and cycloheximide and there was de novo synthesis of several proteins in response to a low-dose priming dose [34] , [35] .…”
Section: Discussionmentioning
confidence: 99%